Psychiatric Training in Pakistan; The Trainees Perspective: A Mixed Method Study - Rida Yaqoob, Maahin Rizwan, Muhammad Mujtaba, Fur Haider, Farasat Ali, Bushra Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Training in Psychiatry, although just like any other specialty training is for 4 years (in case of FCPS) or 5 years (in case of MD). However, it’s very different to other fields of medicine where there is a greater emphasis on physical findings and routine tests. Objective: The aim of this study was to collect the feedback regarding the training program from residents who have just completed training. Material and Method: Two focused group discussions were conducted with residents and young consultants from different cities and in each group at least 6 trainees or young consultants were present. The participants were encouraged to discuss openly about their experiences regarding training. The sessions were held twice each and only finished after data saturation was achieved. As a result of these discussions a detailed questionnaire was developed which was then given to various residents and young consultants all across Pakistan. Results: Among the 70 trainees who filled the questionnaire, the results showed that majority of the trainees were satisfied with their supervisor in terms of knowledge, competency and willingness to teach. Furthermore, they also felt adequately supported by their supervisor when conducting research projects. An overwhelming majority did not suffer from harassment of physical, emotional or sexual nature during their training, nor were they subjected to any bias with respect to, religion or ethnic background, and also felt that the training was not too burdensome on their personal life. Conclusion: The trainees were satisfied on the whole with the supervisors knowledge, competency and the layout of the training program. However, the lagging aspects included applications of psychological interventions. Also the environment of training was found out to be supportive in the study but there was a significant stigma associated with this field.